Towards Parity Democracy in Latin America? Ineffective Strategies and Failed Expectations - Gilas, Karolina Monika (2016)
The construction of parity democracy requires the recognition of rights of all people, regardless of gender. This recognition, in turn, implies the guarantee of full capacity to exercise those rights. Literature and political discourse have argued that the route to equality and parity democracy goes through politics and elections, and that the increase in political representation of women sooner or later will lead us to a real change in their situation and to implementation of public policies with a gender perspective. Many countries, including all the countries in the region, supported gender quotas as an effective and fast-track mechanism to achieve descriptive representation of women. However, after more than twenty five years of affirmative action, the reality of the region denies that idea. Parity democracy is not being achieved through the electoral route. At least, not exclusively via quotas.